Behavioral Drivers of Food Waste Reduction in Urban Vietnam - Nguyen, Thi Thuy Giang; Nguyen, Gia Hung (The Journal of Behavioral Science, 2025)
Background/Problem: Rapid urbanization in Vietnam has intensified challenges in household food waste management, contributing to environmental and economic burdens. Understanding behavioral factors influencing waste reduction is essential for effective interventions. Objective: This study investigates the role of perceived behavioral control (PBC), attitudes, subjective norms and lack of concern within an extended theory of planned behavior (TPB) framework in shaping food waste reduction intentions and behaviors. Design and Methodology: Data were collected from 425urban households in Ho Chi Minh City through an online survey. Partial least squares structural equation modeling was employed to analyze the relationships between the variables. Results: The perceived behavioral control emerged as the strongest predictor of food waste reduction behaviors (β = .26, p < .001), surpassing the influence of attitudes (β = .15, p < .001) and subjective norms (β = .23, p < .001). Lack of concern negatively affected PBC (β = -.37, p < .001) and waste reduction intentions (β = -.31, p < .001), highlighting significant psychological barriers. Conclusion and Implications: The findings underscore the centrality of PBC in driving sustainable household practices and the critical role of addressing barriers such as lack of concern. This study advances the TPB by contextualizing behavioral drivers in rapidly urbanizing economies. Practical insights for policymakers include enhancing food management skills and integrating behavioral insights into policies to promote effective waste management and broader sustainability goals.